Implementation of Arabic Language Learning Using Canva Application and Singing Method - Abdul Azis; Muhammad Mugni Assapari (Journal La Edusci, 2026)
This paper addresses how the Arabic language is learned using the Canva application and the singing technique in Al Badriyah Islamic Boarding School in East Lombok and Assaddiyah Islamic Boarding School in North Lombok. Qualitative method with multi site case study design was used in the study. The data were gathered by observing classes, conducting semi structured interviews and documentation. According to the findings, Canva assisted teachers in delivering the Arabic vocabulary and sentence structure in a more structured, visual, and accessible format, which allowed the students to pay more attention to lessons and comprehend the learning materials easier. The singing technique enhanced a more relaxed and participatory classroom environment by making students repeat vocabulary and basic grammatical patterns with more confidence and less anxiety. The visual media and the musical repetition also enhanced the level of student motivation, classroom participation, and progressive acquisition of vocabulary and mastering of sentence structure. Also, the implementation stimulated more creativity of teachers in creating learning materials and promoted more active engagement of santri in classroom activities. This notwithstanding, the study also found some difficulties, especially lack of access to digital devices, poor and unreliable internet connection, and preliminary hesitation of teachers to utilize digital media. All in all, the research finds out that learning Arabic language in pesantren can be made more engaging, student centered, and responsive to pedagogy through the integration of digital visual media and the application of creative teaching approaches.